1996
DOI: 10.1177/0887302x9601400307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Functional Fit of Chemical Protective Gloves for Agricultural Workers

Abstract: The purpose of this study was to evaluate the functional fit of commercially available protective gloves recommended to agricultural workers and to investigate the effect of polymer type, thickness of glove materials, and glove shape on such fit. The study was conducted in two parts. First the hand dimensions of the user population were estimated by conducting an anthropometric survey of 380 agricultural workers. This was followed by a fit evaluation of four test gloves by 38 farmers whose hand dimensions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Further, as weight and height increased, comfort was anticipated to decrease, because of a rise in sizing and fitting issues. Previous comfort studies indicated that garment fit and fabric properties influenced wearer comfort (Tremblay-Lutter et al 1996, Wheat and Dickson 1999, Barker 2002, Horridge et al 2002. Therefore, comfort was expected to be significantly impacted by satisfaction with the clothing system as a whole, as well as specific clothing attributes of ballistic vest fit and properties.…”
Section: Clothing Comfortmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, as weight and height increased, comfort was anticipated to decrease, because of a rise in sizing and fitting issues. Previous comfort studies indicated that garment fit and fabric properties influenced wearer comfort (Tremblay-Lutter et al 1996, Wheat and Dickson 1999, Barker 2002, Horridge et al 2002. Therefore, comfort was expected to be significantly impacted by satisfaction with the clothing system as a whole, as well as specific clothing attributes of ballistic vest fit and properties.…”
Section: Clothing Comfortmentioning
confidence: 97%
“…Although this study evaluated ballistic vest fit separately from ballistic vest properties, they are closely related, which may explain why both relationships proved significant. For example, a study of gloves (Tremblay-Lutter et al 1996) identified significant differences in fit based on polymer type, fabric thickness and glove shape. The study also showed that gloves that fit better improved wearer dexterity (mobility).…”
Section: Clothing Attributesmentioning
confidence: 98%
See 1 more Smart Citation
“…Garment shape, along with flexibility and thickness of material, may affect evaluations of fit (and consequently protection) of gloves designed for pesticide application by farm workers (Tremblay-Lutter, Crown, & Rigakis, 1996). Formal qualities of the product may offer a measure of protection from physical harm or may create potential danger.…”
Section: Formal Benefits and Instrumental Valuementioning
confidence: 99%
“…The spongy texture of a neoprene wet suit may help a swimmer stay buoyant and regulate body temperature during a triathlon swimming event. Garment shape, along with flexibility and thickness of material, may affect evaluations of fit (and consequently protection) of gloves designed for pesticide application by farm workers (Tremblay-Lutter, Crown, & Rigakis, 1996).…”
Section: Formal Benefits and Instrumental Valuementioning
confidence: 99%